PHARMACOGNOSTICAL EVALUATION OF DIFFERENT PARTS OF APAMARGA (ACHYRANTHES ASPERA LINN.) - Kumar Sanger, *Rupesh; Chandra Singh, Dinesh; Gakkhar, Anup Kumar; Chaubey, Suresh (International Journal of Ayurveda and Pharma Research, 2017)
Plants continue to serve as possible sources for new drugs and chemicals derived from various parts of plants. Nowadays adulteration of crude herbal drugs is very common due to scarcity of drug and its high price prevailing in the market. These herbal medicines can stand in commercial market only if they are evaluated according to modern science. Evaluation of herb involves confirmation of its identity, determination of its quality and purity, and detection of nature of adulteration. So before utilizing a drug for therapeutic purpose, detail pharmacognostical study is essential as it not only helps in correct identification of the drug but also to get a clue for its phytochemicals, pharmacological activities and medicinal properties. API (Ayurvedic Pharmacopoeia of India) has provided standards for a number of plants. But for Apamarga standards are given only for roots and Panchanga (Whole plant), not for the other parts like seeds, leaf and stems which are also used on a large scale for different medicinal properties. Standards are required to be developed for each and every part of the Apamarga. Genuine samples of different parts of Achyranthes aspera Linn was taken to set the standard for each and every part of Apamarga used for medicinal properties. The collected genuine samples were then subjected to macroscopic, microscopy, physicochemical, phytochemical and chromatographic study. Now a day most of the pharmaceutical companies are dealing with plant extracts and Ayurvedic Vaidyas too prefer using single drug extract instead of multiple drug formulations and are getting great response from the patients.